A novel approach for using dielectric spectroscopy to predict viable cell volume (VCV) in early process development. (11th January 2014) - Downey, Brandon J.; Graham, Lisa J.; Breit, Jeffrey F.; Glutting, Nathaniel K.
<x xml:space="preserve">Abstract</x> Online monitoring of viable cell volume (VCV) is essential to the development, monitoring, and control of bioprocesses. The commercial availability of steam‐sterilizable dielectric‐spectroscopy probes has enabled successful adoption of this technology as a key noninvasive method to measure VCV for cell‐culture processes. Technological challenges still exist, however. For some cell lines, the technique's accuracy in predicting the VCV from probe‐permittivity measurements declines as the viability of the cell culture decreases. To investigate the cause of this decrease in accuracy, divergences in predicted vs. actual VCV measurements were directly related to the shape of dielectric frequency scans collected during a cell culture. The changes in the shape of the beta dispersion, which are associated with changes in cell state, are quantified by applying a novel "area ratio" (AR) metric to frequency‐scanning data from the dielectric‐spectroscopy probes. The AR metric is then used to relate the shape of the beta dispersion to single‐frequency permittivity measurements to accurately predict the offline VCV throughout an entire fed‐batch run, regardless of cell state. This work demonstrates the possible feasibility of quantifying the shape of the beta dispersion, determined from frequency‐scanning data, for enhanced measurement of VCV in mammalian cell cultures by applying a novel shape‐characterization technique. In addition, this work demonstrates the utility of using changes in the shape of the beta dispersion to quantify cell health. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:479–487, 2014